2016
DOI: 10.3390/su8101010
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Sustainable Entrepreneurship in Small and Medium-Sized Enterprises in Iran: A Case Study of Food Industry

Abstract: Abstract:This study sought to establish the social and environmental factors that influence sustainable entrepreneurship (SE) in Small-and medium-sized enterprises (SMEs). It also attempted to identify whether the demographic background of the entrepreneur influences the SE in SMEs of the Iranian food industry. A mixed method approach, employing the use of questionnaires and interviews from a sample size of approximately 130 participants and 12 owner-managers of SMEs in food industry, was used to collect data.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(101 citation statements)
references
References 44 publications
4
92
2
3
Order By: Relevance
“…Thus, the control variables do no influence recognition of sustainable opportunities. This is partially consistent with other studies [43,44,[156][157][158][159][160]. Results are shown in Table 9.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, the control variables do no influence recognition of sustainable opportunities. This is partially consistent with other studies [43,44,[156][157][158][159][160]. Results are shown in Table 9.…”
Section: Resultssupporting
confidence: 92%
“…Environmentally superior products or services have been created by SMEs in industries like constructions [42], food [43] or mining [44]. These firms can in principle be small start-ups, but also large incumbent firms that have significant market share in their industry [27].…”
Section: Sustainable Entrepreneurshipmentioning
confidence: 99%
“…In the Iranian context, survey data from 177 entrepreneurs showed that those entrepreneurs that have other values and that are highly future-oriented have a greater tendency to undertake sustainability-oriented actions [14]. In small-sized enterprises, having behaviorally integrated top management teams [89] and a customer orientation [18] are further reasons explaining why Iranian entrepreneurs pay attention to the surrounding business environment.…”
Section: Discussionmentioning
confidence: 99%
“…As in many other research studies [18,[90][91][92], the cross-sectional nature of the data may limit the assessment of causal relationships in the model. In particular, some caution must be taken in the interpretation of our findings.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
See 1 more Smart Citation